The Effect Of Employer Branding, Salary, And Work-Life Balance On Gen Z's Interest In Applying At Alfamart Modern Retail Store - Cahay, Andika; Afriani, Sulisti; Nurzam, Nurzam (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The purpose of this study was to determine the influence of employer branding, salary, and work-life balance on Gen Z's interest in applying at Alfamart modern retail stores. This research method uses quantitative descriptive research. This research was conducted in Bengkulu City. The sample in this study was 100 Gen Z individuals who were looking for work and applying for positions at Alfamart. The sampling technique used was purposive sampling. Data collection was conducted using a questionnaire with a Likert scale. The data analysis technique used was descriptive quantitative. The results of the study showed that there was a significant influence between employer branding on Gen Z's interest in applying for work at Alfamart with a t-value of 2.100 greater than the t-table of 1.66088 with a significance of 0.038 <0.05. Salary also influenced Gen Z's interest in applying for work at Alfamart with a t-value of 3.083> t-table of 1.66088 and a significance of 0.003 <0.05. In addition, there was a significant influence of work-life balance on Gen Z's interest in applying for work at Alfamart with a t-value of 2.717> t-table of 1.66088 with a significance of 0.008 <0.05. Simultaneously, there was an influence of employer branding, salary, and work-life balance simultaneously on Gen Z's interest in applying for work at Alfamart with an F-value of 19.064> F-table of 2.70 with a significance of 0.000 <0.05. The R-square value of 0.373 indicates that 37.3% of the variation in job application interest is explained by employer branding, salary, and work-life balance, while the remaining 62.7% is influenced by other factors.